Design Analysis of a Kenaf Decorticating Machine - Ibrahim BALA; Solomon M. DAUDA; Audu A. BALAMI; Peter A. IDAH (FUDMA Journal of Engineering and Technology, 2026)
Kenaf (Hibiscus cannabinus L.) is a plant rich with fibre characterised with high growth rate that has the potential to replace synthetic and wood-based fibres. Traditional stalk fibre extraction (which is often manual) are tedious, ineffective and produce fibre qualities that are inconsistent in overall quality. This study describes the design analysis of a kenaf decorticating machine. Major components of the machine were identified and design data generated. Some of the design parameters were established, including the torque, stresses acting on the shafts, the belt tensions, decorticating and crushing forces and the required power needs, so as to increase processing efficiency and fibre yield. With a drum speed of 450 rpm, the machine decorticating force was obtained as 2,780 N, which is significantly greater than the determined crushing force of 695 N. Decortication was anticipated to require 7.9 kW of electricity, however the machine only required 282 W to run, indicating effective mechanical transmission. The pulley system and shaft diameter (35 mm) were selected to reduce energy loss and guarantee long-term operation. The machine has been designed to curtail the limitations of low decortication efficiency, excessive manual input, and safety concerns recorded from existing machines. The machine provides a practical solution for small- to medium-scale kenaf farmers, with the potential to revitalize local fibre industries and reduce environmental reliance on synthetic materials.
Keywords: Decortication force, design analysis, fibre extraction, fibre-rich plant, mechanical transmission.